Inhibition does not affect the timing code for vocalizations in the mouse auditory midbrain - Dimitrov, Alexander G.; Cummins, Graham I.; Mayko, Zachary M.; Portfors, Christine V. (Frontiers in Physiology, 2014)
Many animals use a diverse repertoire of complex acoustic signals to convey different types of information to other animals. The information in each vocalization therefore must be coded by neurons in the auditory system. One way in which the auditory system may discriminate among different vocalizations is by having highly selective neurons, where only one or two different vocalizations evoke a strong response from a single neuron. Another strategy is to have specific spike timing patterns for particular vocalizations such that each neural response can be matched to a specific vocalization. Both of these strategies may occur in the auditory midbrain of mice. However, the neural mechanisms underlying rate and time coding are unclear, but it is likely that inhibition plays a role. Here, we examined whether inhibition is involved in creating neural selectivity to vocalizations via rate and/or time coding in the mouse inferior colliculus. We examined extracellular single unit responses to vocalizations before and after iontophoretically blocking GABA_A and glycine receptors in the IC of awake mice. In general, we found that pharmacologically blocking inhibitory receptors in the IC increased response rate to vocalizations but did not dramatically affect spike timing. We observed two main effects when inhibition was locally blocked: 1) Highly selective neurons maintained their selectivity and the information about the stimuli did not change, but response rate increased slightly. 2) Neurons that responded to vocalizations in the control condition, also responded to the same stimuli in the test condition, with similar timing and pattern, but with a greater number of spikes, and, in some cases, greater reliability. Interestingly, in some neurons, blocking inhibition had no effect on vocalization-evoked responses. Overall, we found that inhibition in the IC does not play a substantial role in creating the reliable neuronal temporal patterns in response to vocalizations.